2015
DOI: 10.1155/2015/684976
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Laparoscopic Salvage of CAPD Catheter Malfunction and Migration: The Santosh-PGI Hanging Loop Technique

Abstract: CAPD catheter malfunction is a common problem. Obstruction due to wrapping by appendices epiploicae of sigmoid colon has been rarely reported in literature. We report a case of CAPD catheter malfunction caused by catheter tip migration and obstruction by appendices epiploicae that was successfully managed by laparoscopic hanging loop technique. This case report highlights the ease with which epiplopexy can be performed and catheter tip migration can be prevented by this innovative laparoscopic procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…have described a novel method of suspending the catheter with two polypropylene sutures passed around it which were fixed to the lower abdominal wall, thereby maintaining the position of the catheter. [ 7 ] Bae et al . proposed that this type of loop fixation is employed at the time of primary laparoscopic insertion and showed that the incidence of catheter migration was significantly lower with this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…have described a novel method of suspending the catheter with two polypropylene sutures passed around it which were fixed to the lower abdominal wall, thereby maintaining the position of the catheter. [ 7 ] Bae et al . proposed that this type of loop fixation is employed at the time of primary laparoscopic insertion and showed that the incidence of catheter migration was significantly lower with this strategy.…”
Section: Discussionmentioning
confidence: 99%